2010
DOI: 10.3109/13813451003652997
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2/TIMP-2/TIMP-4 versus MMP-9/TIMP-3 in transition from compensatory hypertrophy and angiogenesis to decompensatory heart failure*

Abstract: Although matrix metalloproteinase (MMPs) and tissue inhibitor of metalloproteinase (TIMPs) play vital role in tumor angiogenesis and TIMP-3 caused apoptosis, their role in cardiac angiogenesis is unknown. Interestingly, a disruption of coordinated cardiac hypertrophy and angiogenesis contributed to the transition to heart failure, however, the proteolytic and anti-angiogenic mechanisms of transition from compensatory hypertrophy to decompensatory heart failure were unclear. We hypothesized that after an aortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(79 citation statements)
references
References 33 publications
4
75
0
Order By: Relevance
“…TIMP3 is recognized as a multifunctional molecule in cell biology, covering cell differentiation, angiogenesis and immunology. 8,16,17 It has been reported that TIMP3 was involved in cancer apoptosis and invasion. In terms of the status of TIMP3 in cancer, it is also found downregulated in 95.2% clear renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…TIMP3 is recognized as a multifunctional molecule in cell biology, covering cell differentiation, angiogenesis and immunology. 8,16,17 It has been reported that TIMP3 was involved in cancer apoptosis and invasion. In terms of the status of TIMP3 in cancer, it is also found downregulated in 95.2% clear renal cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence shows that MMPs and their physiological inhibitors, TIMPs, play a pivotal role in the cardiac remodeling progress (Spinale, 2007). It was recently reported that the transcriptional levels of MMP-2 were upregulated during the compensatory period and that the expression of MMP-9 was increased during the de-compensatory period (Givvimani et al, 2010). The loss or inhibition of MMP-9 suppresses the LV remodeling and dysfunction after acute pressure overload in mice (Heymans et al, 2005a).…”
Section: Discussionmentioning
confidence: 99%
“…Several MMPs are upregulated in cardiac hypertrophy and an imbalance between MMPs and their endogenous inhibitors (tissue inhibitor of metalloproteinases-TIMPs) may underlie the transition of compensated LVH to dilated LVH. [3][4][5][6][7] In addition, experimental evidence suggests that nonspecific inhibition of MMPs, especially MMP-2, ameliorates hypertensive cardiovascular remodelling. 8 MMPs activities are regulated at different levels including transcription, activation of latent forms of MMPs and inhibition by TIMPs 5,9 In this respect, genetic polymorphisms in MMP-2 gene may also affect MMP-2 expression or activity, as shown in several disease conditions.…”
Section: Introductionmentioning
confidence: 99%